2022
DOI: 10.3389/fped.2022.952703
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between arterial blood pressures and regional cerebral oxygen saturation in preterm neonates during postnatal transition-an observational study

Abstract: ObjectiveTo assess whether blood pressure (systolic (SABP), diastolic (DABP), and mean arterial blood pressure (MABP) and cerebral-regional-oxygen-saturation (crSO2) and cerebral-fractional-tissue-oxygen-extraction (cFTOE) are associated after immediate fetal-to-neonatal transition in preterm neonates with and without respiratory support.Study designPost-hoc analyses of secondary outcome parameters of prospective observational studies were performed. We included moderate and late preterm neonates with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…This difference might be explained due to late and moderate preterm neonates that are less likely to require respiratory support compared with very and extremely preterm neonates. Pfurtscheller et al 27 already showed that late and moderate preterm neonates without respiratory support are capable of maintaining cerebral autoregulation compared with late and moderate preterm neonates with respiratory support that is in line with the present findings.…”
Section: Discussionsupporting
confidence: 93%
“…This difference might be explained due to late and moderate preterm neonates that are less likely to require respiratory support compared with very and extremely preterm neonates. Pfurtscheller et al 27 already showed that late and moderate preterm neonates without respiratory support are capable of maintaining cerebral autoregulation compared with late and moderate preterm neonates with respiratory support that is in line with the present findings.…”
Section: Discussionsupporting
confidence: 93%
“…Blood pressure was measured invasively with an indwelling catheter in 27 [ 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] studies and non-invasively with oscillometric measurements in 3 studies [ 22 , 49 , 50 ]. In five studies [ 51 , 52 , 53 , 54 , 55 ], both methods were combined, and in one study [ 56 ], the method was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies described the association of blood pressure values and cerebral NIRS during immediate transition in preterm and in term neonates [ 22 , 50 ] ( Table 1 ). These studies showed intact cerebral autoregulation in term neonates and impaired cerebral autoregulation in moderate and late preterm neonates receiving respiratory support with significant associations between crSO2/cFTOE and MABP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired cerebrovascular autoregulation leads to a pressure-dependent CBF due to its linear correlation with CPP, resulting in deleterious CBF fluctuations in response to CPP variations ( 12 , 25 28 ). Several studies have already indicated impaired cerebrovascular autoregulation in compromised preterm neonates ( 25 27 , 29 33 ). Considering that in the present study cFTOE also tends to be associated with lactate in preterm neonates, low crSO 2 may not only be a result of diminished oxygen content -in terms of low SpO 2 -, but also due to increased oxygen extraction in the cerebral microcirculation.…”
Section: Discussionmentioning
confidence: 99%